Qur’anic Healing Therapy pada Lansia Gangguan Depresi (Jurusan Bimbingan dan Konseling Islam, 2018)
Depression is a vulnerable psychological disorder among the elderly. Qualitative research with case study at Panti Tresna Werdha Hargo Dedali Surabaya explains the size of elderly depression, the dynamics before and after therapy, and the implications on some psychological aspects by using qur'ani healing therapy (healing therapy qur'an). This data collection involves three elderly people using observation, in-depth interviews, and Beck depression Inventory (BDI). The results of this study indicate the size of the elderly depression that is the subject of this study is moderate and mild. The way qur'ani therapy used in this case has implications for cognitive, affective, and motoric health of the elderly.